Năng lực số của học sinh trung học phổ thông ở Việt Nam - Trịnh , Thị Phương Thảo; Trịnh , Thanh Hải; Lê, Minh Cường; Đỗ , Bảo Châu; Trần, Trung (Tạp chí Giáo dục, 2024)
In the context of robust digital transformation in many fields, including education, the issue of developing digital competencies for learners is an important and urgent issue. Consequently, it is necessary for training at educational institutions to focus on developing digital competencies for pedagogical students, i.e. prospective teachers. The article, based on the analysis of domestic and international research, introduces the concept of digital competence and presents the digital competence framework of some organizations. The authors also propose a digital competency framework for university students majoring in primary education with the hope to provide a basis for developing appropriate training programs in the current digital transformation era. The research results can hopefully serve as a reference for digital competencies-based teaching and education and a premise for building training programs and fostering digital competencies for pedagogical students in training establishments and teachers at all school levels.